Analisis Implementasi Kepatuhan Syariah Pada Pembiayaan Hybrid Contract di BPRS Puduarta Insani - Siti Rahma, Mawadda; S.E.I, M.E.I, Nurul Jannah, (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study focuses on the regulations issued by the MUI DSN and the implementation of the BPRS Puduarta Insani institution, especially on sharia compliance in hybrid contract financing. source of data from the leaders and members of the BPRS. The MUI DSN Fatwa is required for every Islamic financial industry, in this case BPRS, to comply with sharia provisions which make sharia supervision an inseparable part of sharia compliance. This can be seen from several regulations issued by the DSN MUI which become a reference for the Islamic finance industry in carrying out its activities in the field of Islamic finance. This research is a field research with a descriptive qualitative approach. The data analysis technique uses data reduction techniques. The results of the analysis show that: that there are terms and conditions for murabahah bil wakalah financing which are contained in 22 articles that are set out from financing provisions to completion in murabahah bil wakalah financing. The implementation of murabahah bil wakalah at BPRS Puduarta Insani is fully in accordance with the provisions of the DSN-MUI Fatwa No. 04 of 2000 concerning murabaha.